Pengaruh Konten Pemasaran dan E-Wom pada Media Sosial Tiktok Shop terhadap Keputusan Pembelian Generasi Z di Kabupaten Karawang - Putri, Tiara Brescia; Savitri, Citra; Fadilla, Syifa Pramudita (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to investigate the impact of marketing content and e-word of mouth (E-Wom) on purchasing decisions in the context of the TikTok Shop application in Generation Z. The population that is the focus of research is Generation Z who have made transactions through TikTok Shop on their smartphone devices. From a total population of 132,325, 80 respondents were selected for this study using cluster sampling. Data is collected through the use of questionnaires disseminated through the Google Forms platform. Data analysis was performed using (SEM) using Smart PLS 3 devices. The results showed that marketing content has a positive influence on purchasing decisions, and E-Wom has a significant influence on purchasing decisions.